1999
DOI: 10.1002/(sici)1098-2795(199908)53:4<384::aid-mrd3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Antisteroidal compounds and steroid withdrawal down-regulate cadherin-11 mRNA and protein expression levels in human endometrial stromal cells undergoing decidualisation in vitro

Abstract: The cellular mechanisms by which steroids and antisteroidal compounds modulate the function and/or integrity of the human endometrium remain poorly understood. We recently determined that the expression of the novel cadherin subtype, known as cadherin‐11, is tightly regulated in endometrial stromal cells undergoing decidualisation in vivo and in vitro. To determine whether the actions of antisteroids on the endometrium are mediated, at least in part, by their ability to regulate the expression of this cell adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…They found that progesterone, but not E2 or dihydroestosterone, was capable of regulating Cad-11 expression. However, E2 was capable of potentiating the stimulating effects of progesterone in a dose-dependent manner [172,173], and that the antiestrogen, ICI182780, was capable of reducing Cad-11 expression in these cells, suggesting the requirement of estrogens and ERs in mediating these effects [174]. Gorodeski [175] studied the effects of estrogens and aging on paracellular permeability of human vaginal-cervical epithelia by determining the transepithelial electrical conductance (TEC) across cultures of normal human ectocervical epithelial cells on filters.…”
Section: Estrogens and Ers Are Involved In The Regulation Of Tight Anmentioning
confidence: 96%
See 2 more Smart Citations
“…They found that progesterone, but not E2 or dihydroestosterone, was capable of regulating Cad-11 expression. However, E2 was capable of potentiating the stimulating effects of progesterone in a dose-dependent manner [172,173], and that the antiestrogen, ICI182780, was capable of reducing Cad-11 expression in these cells, suggesting the requirement of estrogens and ERs in mediating these effects [174]. Gorodeski [175] studied the effects of estrogens and aging on paracellular permeability of human vaginal-cervical epithelia by determining the transepithelial electrical conductance (TEC) across cultures of normal human ectocervical epithelial cells on filters.…”
Section: Estrogens and Ers Are Involved In The Regulation Of Tight Anmentioning
confidence: 96%
“…if it is involved inhibition of E2-Induced activation of MAPK pathway; Second, both ERs [188][189][190] and Na + , K + -ATPase [117,142,191] are known to be involved in the regulation of NF-jB, a pleiotropic transcriptional factor involved in the regulation of diverse biological processes such as apoptosis, cell survival, cell growth and cell division in normal and various cancers including breast cancer [192][193][194]. It will be also interesting to determine if ouabain is involved in the regulation of both ER-and Na + , K + -ATPase-mediated regulation of NF-jB in breast cancer cells; Third, both ERs [174,177] and Na + , K + -ATPase [43,55,61,76,84] are known to play key role in the regulation of TJs and AJs. Aberrant (usually reduced or loss) expression of various components of TJs and AJs has been frequently observed in breast cancer cells [70,87,98].…”
Section: A Novel Concept and A New Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…Because aberrant expression of P-cadherin identified a subgroup of estrogen receptor-␣-negative breast carcinomas (16), we raised the hypothesis that the expression of P-cadherin in mammary epithelial cells is hormonally regulated, as described for E-cadherin (20), Ncadherin (21), and cadherin-11 (22).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cadherin-11 is also expressed in the alveolar macrophages of patients with pulmonary fibrosis (24). Meanwhile, estradiol can regulate cadherin-11 expression in human endometrial stromal cells (25,26) and in neurons of macaques (27). Therefore, we further hypothesized that estrogen might promote M1/M2 macrophage polarization through potentiating cadherin-11 to aggravate joint inflammation.…”
mentioning
confidence: 98%